Optimize Productive Zakat to Eradicate Poverty - Ramadhani, Rega; Mahbubi, Rafli; Syarah, Syarah (Bulletin of Islamic Economics, 2023)
This article discusses how the use of productive zakat can have a major impact on the macro economy, especially in minimizing poverty that is rife in society in a country. This study uses a qualitative method with a literature study approach. The type of data is in the form of narrative, the data source is in the form of publications, both physical print and online. This paper finds that the optimization of productive zakat carried out by institutions that specifically handle the distribution of zakat, can be one of the stimuluses for assistance to people (mustahik) in need, which can raise the standard of living to be better than before. So that in the end the distribution of productive zakat is expected to have an impact on reducing and anticipating poverty that occurs.